A Case Report of Streptomycin Induced Cochlear Toxicity in Tuberculosis Patients - Jha, Ambika Nand; Shah, Akshay H; Trivedi, Upama N; Patel, Jignesh S (Bangladesh Journal of Infectious Diseases, 2021)
Streptomycin is a semi-synthetic, oldest aminoglycoside. It is the first line drug for tuberculosis. It may adversely produce ototoxicity, nephrotoxicity, neuromuscular blockage. The initial isolation of streptomycin from Streptomyces griseus. A 51 year old female visited to the medicine OPD in hospital. On presentation she complained of vomiting and vertigo from last few days. The patient recently diagnosed for Pulmonary TB by chest X-ray 3 month back. She taken streptomycin 0.75mg IV bid. As these were the new symptoms, the physician requested for otolaryngologist consultation to rule out the other causes and was insignificant. But the audiometry report showed hearing loss. The ototoxicity caused by aminoglycosides is permanent and can negatively affect the individual’s quality of life. The early detection, management and therapeutic approaches for prevention of hearing loss is crucial. Reporting here is an interesting case of streptomycin induced cochlear toxicity. Bangladesh Journal of Infectious Diseases 2020;7(2):99-101